Aberrant X chromosomal rearrangement through multi‐step template switching during sister chromatid formation in a patient with severe hemophilia A. Issue 9 (5th July 2020) - Tokoro, Mahiru; Tamura, Shogo; Suzuki, Nobuaki; Kakihara, Misaki; Hattori, Yuna; Odaira, Koya; Suzuki, Sachiko; Takagi, Akira; Katsumi, Akira; Hayakawa, Fumihiko; Okamoto, Shuichi; Suzuki, Atsuo; et al.
Abstract: Background: Hemophilia A (HA) is an X‐linked recessive bleeding disorder caused by pathogenic variants of the coagulation factor VIII gene ( F8 ). Half of the patients with severe HA have a recurrent inversion in the X chromosome, that is, F8 intron 22 or intron 1 inversion. Here, we characterized an abnormal F8 due to atypical complex X chromosome rearrangements in a Japanese patient with severe HA. Methods: Recurrent F8 inversions were tested with inverse shifting‐PCR. The genomic structure was investigated using PCR‐based direct sequencing or quantitative PCR. Results: The proband's X chromosome had a 119.5 kb insertion, a reverse duplex of an extragenic sequence on the F8 telomere region into the F8 intron 1 with two breakpoints. The telomeric breakpoint was a joining from the F8 intron 1 to the inverted FUNDC2 via a two‐base microhomology, and the centromeric breakpoint was a recombination between F8 intron 1 homologous sequences. The rearrangement mechanism was suggested as a multi‐step rearrangement with template switching such as fork stalling and template switching (FoSTeS)/microhomology‐mediated break‐induced replication (MMBIR) and/or homologous sequence‐associated recombination during a sister chromatid formation. Conclusion: We identified the aberrant X chromosome with a split F8 due to a multi‐step rearrangement in a patient with severe HA. Abstract : Hemophilia A (HA) is an X‐linked recessive bleeding disorder caused by mutations in the coagulation factor VIII gene ( F8 ). We identified the aberrant chromosome X with a split F8 due to a multi‐step rearrangement in a severe HA patient. The rearrangement mechanism was suggested as a multi‐step rearrangement with template switching such as FoSTeS/MMBIR and/or homologous sequence associating recombination during a sister chromatid formation.